2017
DOI: 10.1002/cncr.30656
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in adolescents and young adults: Who remains at risk of poor social functioning over time?

Abstract: Although improved over time, social functioning still was found to be compromised 24 months after the primary diagnosis. Nearly one-third of these patients remain at risk of poor social functioning. Reducing physical symptoms and psychological distress and enhancing social support by interventions during the period after treatment may potentially help these young survivors to better reintegrate into society. Cancer 2017;123:2743-51. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 30 publications
5
72
0
Order By: Relevance
“…Adolescence and young adulthood are stages in life with increased vulnerability to stress. This vulnerability results in even greater psychosocial needs among AYA with a history of cancer, [46][47][48][49] with studies reporting poorer mental health, 47 health-related quality of life [50][51][52] and social functioning, 53 as well as 2.5 times more fatigue. 54 These challenges, which occur throughout the cancer care continuum (ie, from diagnosis to survivorship or end of life), span several domains of stress and coping, 55 and post-traumatic stress disorder (PTSD) [68][69][70] have also been noted in this population.…”
Section: Psychosocial Outcomesmentioning
confidence: 99%
“…Adolescence and young adulthood are stages in life with increased vulnerability to stress. This vulnerability results in even greater psychosocial needs among AYA with a history of cancer, [46][47][48][49] with studies reporting poorer mental health, 47 health-related quality of life [50][51][52] and social functioning, 53 as well as 2.5 times more fatigue. 54 These challenges, which occur throughout the cancer care continuum (ie, from diagnosis to survivorship or end of life), span several domains of stress and coping, 55 and post-traumatic stress disorder (PTSD) [68][69][70] have also been noted in this population.…”
Section: Psychosocial Outcomesmentioning
confidence: 99%
“…AYAs with cancer frequently report difficulties in maintaining or making new social relationships because of the long-term effects of treatment or feeling anxious concerning fitting into their peer group again [26,27]. Husson et al [28] found that AYAs with cancer who had low social functioning reported more physical symptoms and higher levels of distress, and they perceived themselves to receive less social support. We also found that single patients and patients who don't have any children had more unmet needs in several items of psychological needs, physical and daily living needs, and health system and information needs.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recent research examining the social functioning of AYAs over time suggests that improvements in social functioning usually take place within the first year post-diagnosis and that on average no significant additional improvements occur between 12 and 24 months. 5 AYA cancer survivors who consistently scored low on measures of social functioning reported more physical symptoms and higher levels of psychological distress. 5 Research examining the links between sociodemographic and medical factors and AYA cancer survivor outcomes suggests that female gender, the diagnosis of a hematological disorder, hematopoietic stem cell transplantation, and a shorter off-treatment period are risk variables for poorer health-related quality of life and social functioning among AYA cancer survivors.…”
Section: Introductionmentioning
confidence: 95%
“…5 AYA cancer survivors who consistently scored low on measures of social functioning reported more physical symptoms and higher levels of psychological distress. 5 Research examining the links between sociodemographic and medical factors and AYA cancer survivor outcomes suggests that female gender, the diagnosis of a hematological disorder, hematopoietic stem cell transplantation, and a shorter off-treatment period are risk variables for poorer health-related quality of life and social functioning among AYA cancer survivors. 6 During the transition to survivorship care, there are unique challenges, including redefining ''normalcy,'' reconnecting with family and peers, and managing fear and uncertainty associated with follow-up procedures and risk of cancer recurrence.…”
Section: Introductionmentioning
confidence: 95%